Political ideology of the board and CEO dismissal following financial misconduct - PARK, Uisung (Institutional Knowledge at Singapore Management University, 2020)
Why do some boards refuse to take serious action against CEOs who have committed financial misconduct? Past work has directed attention to the antecedents of misconduct while largely overlooking this question. The relatively few studies to examine it have typically revolved around the capacity of boards to take action, or their relationships to their CEOs. This study instead examines how the beliefs and values held by board members can influence their actions following financial misconduct. Focusing on political ideology, we argue and find that politically conservative boards are more likely to respond by dismissing the CEO than are liberal boards. In addition, we identify two factors that moderate this finding: a firm’s ethical shortfall compare to industry peers and engagement in corporate social responsibility.